The Role of Competency and Compensation Required by the Police to Face Performance Demands in the Society 5.0 Era - Fazri Romadhon; Pantius Drahen Soeling (Dinasti International Journal of Education Management And Social Science, 2024)
The performance of police officers continues to be required to increase due to developments, particularly in the Society 5.0 era. In this context, competence and compensation are two consider determinant factors to study. The objectives of this study are to analyze the importance of competency and compensation required by the police in facing performance demands in the Society 5.0 era. A qualitative approach was carried out with data collected secondarily from various literature that was then analyzed using qualitative data analysis techniques. The results show that to perform, police are required to have competencies that are in line with the Society 5.0 era by combining hard skills, soft skills, ICT processing skills, and knowledge in the form of (1) digital competence in a technology-based work environment, (2) collaboration with systems cyber, (3) flexible work processes that can be adjusted to stakeholder needs, (4) having a competitive mentality, and (5) teamwork. In addition, the pay that police officers receive has a significant impact on their performance since it influences their motivation, the in-role and extra-role behaviors they engage in at work, and the demands of adapting to the demands of the Society 5.0 era.